Improvement of Critical Attitude after Using Worksheet Web Based on Socio-Scientifi Issues (SSI) - Hanis Pramudawardani; Linda Kusumawati; Musawwir Usman; Nurfiah (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2026)
Critical attitude is an important 21st-century competency that supports analytical and decision-making skills. Observations show that students are still passive in learning, such as being reluctant to ask and answer questions, indicating that critical attitude is still low. This study aims to determine the effectiveness of improving critical attitude using worksheets web-based Socio-Scientific Issues (SSI) that have been developed previously on environmental pollution. The research method uses a quantitative approach using a one-group pretest and posttest experimental design. The study was conducted on eighth-grade junior high school students on environmental pollution material. The study was conducted at SMP 1 Suruh Trenggalek. The data analysis technique used was the N-gain test. The critical attitude instrument includes four indicators: truth-seeking, open-mindedness, confidence in reasoning, and cognitive maturity. The results showed an n-gain value of 0.32 (moderate category). The highest sub-indicator was cognitive maturity, while confidence in reasoning was the lowest. These findings prove that the use of worksheets web-based SSI-based is effective in improving students' critical attitude, although optimization is needed in the confidence in reasoning aspect.